Pengembangan Aplikasi Regresi Parameter Cuaca Berbasis Visual Basic For Application - Bayu Bagus Riyandiarto; Nanda Noor Fadjrin (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Abstract — This research is the development of the Microsoft Excel VBA application to perform regression analysis between weather parameters in terms of data centering measures (PAMER11). The combination of parameters and data centering measures obtained 55 parameters that can be combined into 1,677,255,139,725 annual regression analysis outputs. The case study used in this study only calculates air humidity with temperature and air pressure observation variables, then the analysis results are compared with the results of the Excel Toolpak analysis data with the Anova. The development of this application method is carried out in 4 stages, namely: define, design, develop, adn dissemination. The defined stage includes analysis of the needs of researchers in the BMKG field, analysis coverage of the needs of BMKG in the form of regression analysis. The design stage includes format selection, application program selection, and initial design (prototype 1). The development stage includes validation (prototype 2) obtained a programming aspect value of 4.1325 valid criteria, comparison of Anova results from the output of the PAMER11 application and analysis of the Excel toolpak, the f-value is with a p-value of 99% which results in the two calculations are significantly equal, for the display aspect get a value of 4,8175 valid criteria, limited and field product trials (prototype 3), where a limited trial was carried out on all faculty lecturers getting a score of 4.2440 very good criteria. Field trials conducted on the BMKG Cilacap got a score of 4.8333 very good criteria and data analysis at each stage of development has been improved towards the application program. Keywords — Development; Microsoft Excel; Visual Basic for Application (VBA); Regression Analysis; Weather Parameters